Membangun Kepercayaan Masyarakat Strategi Komunikasi Organisasi BAZNAS Sumatera Utara dalam Penghimpunan Zakat - Harahap, Azrai; Syukur Kholil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The organizational communication strategy used by BAZNAS North Sumatra to strengthen public trust and increase participation in zakat collection. Public trust is considered a key factor in encouraging participation in zakat payments through these official institutions. The research method used is a qualitative approach with case studies, involving in-depth interviews, observation and document analysis. The research results show that BAZNAS North Sumatra implements various communication strategies, such as media campaigns, outreach, report transparency, service improvement, as well as involvement and partnerships with the community. This strategy plays a role in increasing credibility, organizational trust and public trust in BAZNAS North Sumatra. Organizational communication activities, including internal, external communications, public relations management, and crisis communications, also play an important role in strengthening public trust. In addition, effective marketing communications, such as advertising, sales promotions, public relations, and direct marketing, also have a positive impact on increasing public trust and participation in zakat collection. The increase in public trust built through a comprehensive communication strategy has had an impact on increasing the number of muzaki who entrust their zakat to BAZNAS North Sumatra in recent years.